2022
DOI: 10.3390/seeds1030018
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Germination of Erythrina velutina Seeds under a Different Imbibition Period in Gibberellin

Abstract: The knowledge of the physiological aspects of Caatinga’s vegetal species is extremely important for preserving this biome, which suffers with human impacts, mainly to select propagation methods. Erythrina velutina is a Brazilian tree, generally found in Caatinga, with medical and forestry potential. The objective of this paper was to determine the best soaking period in gibberellin solution to achieve the highest germination and to evaluate the internal anatomy by digital microtomography of E. velutina seeds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Similar results were obtained by Stejskalová et al (2015) in sycamore seeds. Contrastingly, there are many studies that have demonstrated improved seed germination by treatment with GA 3 (Gashi et al, 2019;Cornea-Cipcigan et al, 2020;Uçarli, 2021;Guariz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Stejskalová et al (2015) in sycamore seeds. Contrastingly, there are many studies that have demonstrated improved seed germination by treatment with GA 3 (Gashi et al, 2019;Cornea-Cipcigan et al, 2020;Uçarli, 2021;Guariz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between levels of hormones, enzymes and moisture have a fundamental role in the seed germination (Guariz et al, 2022). NO has a positive effect on several plant cellular procedures, including: Breaking seed dormancy, growth and plant defense against stress.…”
Section: Introductionmentioning
confidence: 99%